Influence of Skin-to-Skin Contact and Rooming-In on Early Mother–Infant Interaction: A Randomized Controlled Trial. (August 2013) - Dumas, Louise; Lepage, Mario; Bystrova, Ksenia; Matthiesen, Ann-Sofi; Welles-Nyström, Barbara; Widström, Ann-Marie
The objective of this research was to study influence of birth routines on mother–infant interaction at Day 4. The present research is part of a longitudinal study where mother–infant pairs were randomized by infant location and apparel. We intended to assess mother–infant interaction from videos filmed at Day 4. A protocol for the assessment/coding of the affective quality of maternal behaviors indicative of early mother–infant interaction was developed and interculturally validated. Results were compared with birth randomization, as to explain impact of birth practices. Findings indicate that separation and swaddling at birth interfered with mother–infant interaction during a breastfeeding session at Day 4; these mothers significantly demonstrated more roughness in their behaviors with their infants at Day 4. Results also show evidences of a sensitive period for separation after birth. Implications are to encourage immediate and uninterrupted skin-to-skin contact at birth, and rooming-in during postpartum, as recommended in World Health Organization/UNICEF Ten Steps for Successful Breastfeeding .